Peace Narratives as a Strategy for Digital Conflict Resolution After Indonesia’s 2024 Elections - Dewi Setyorini, Islamia; Risma Saragih, Herlina Juni; Malik, Ichsan; Setiawibawa, Rachmat; Uksan, Arifuddin (Cita konsultindo, 2025)
This study examines the role of peaceful narratives as a conflict resolution strategy in the digital arena following Indonesia's 2024 general elections. Amidst rising political polarization, especially among youth active on social media platforms such as TikTok and X (formerly Twitter), digital spaces have become arenas for both political expression and social division. The research applies qualitative content analysis to explore how